1997
DOI: 10.1521/pedi.1997.11.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Significance of Associations Between Childhood Trauma and Borderline Personality Disorder: Conceptual and Clinical Implications

Abstract: Numerous studies over the past decade have pointed to the fre quent occurrence of trauma and neglect in the childhood expe rience of patients with Borderline Personality Disorder (BPD). Advancing research on Posttraumatic Stress Disorder (PTSD) and Dissociative Disorders offers further insight into under standing shared clinical phenomena with BPD. Drawing upon attachment theory, models of learned helplessness, and early primate deprivation, empirical, theoretical and clinical data are integrated to conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
3
11

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 32 publications
4
70
3
11
Order By: Relevance
“…North American and Western European studies have provided a large body of evidence on the numerous intrafamilial pathological childhood experiences, such as a history of physical, emotional, sexual abuse and neglect that are commonly reported by borderline patients 1,[4][5][6] . More specifically, 40-86% of subjects with BPD have reported being sexually abused during their childhood [7][8][9][10][11][12][13][14] , to a maximum of 94.7% reported by McLean and Gallop in 2003 15 .…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…North American and Western European studies have provided a large body of evidence on the numerous intrafamilial pathological childhood experiences, such as a history of physical, emotional, sexual abuse and neglect that are commonly reported by borderline patients 1,[4][5][6] . More specifically, 40-86% of subjects with BPD have reported being sexually abused during their childhood [7][8][9][10][11][12][13][14] , to a maximum of 94.7% reported by McLean and Gallop in 2003 15 .…”
Section: Background and Objectivesmentioning
confidence: 99%
“…A meta-analytic study of the published literature (containing 19 North-American and two European studies) before 1999, conducted by Fossati, Mededdu and Maffei 25 , has found that in Western society there is only a moderate association between childhood sexual abuse and BPD diagnosis. Sexual abuse does not occur in a vacuum, it occurs in the context of other forms of abuse and dysfunctional parental behavior 26,27 and contributes to the development of BPD through interaction with other pathological childhood experiences 4,5 . For example, sexually abused BPD patients are more likely to report physical neglect, emotional withdrawal, and inconsistent treatment by caretakers 13 .…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Notamment, les difficultés sociales des céré -brolésés traumatiques orbitaux frontaux sont relativement stables 2 , sauf pour les cas de démences fronto-temporales, alors que celles des personnes avec un TPL ont tendance à varier dans le temps en fonction des stresseurs interpersonnels plus spécifiques. Aussi il est important de rappeler que le TPL est d'origine neurodéveloppementale et non la consé quence directe d'un trauma cérébral spécifique (Sabo, 1997). À cet effet, Mesulam (2002) souligne que chez des individus « neurologiquement intacts », mais avec un faible degré d'intégration neuronale, il est possible d'observer la résurgence de tendances comportementales latentes 3 qui rappellent étrangement les conséquences d'une lésion frontale.…”
Section: Graphique 1 Les Lobes Frontaux Du Cortex Cérébralunclassified
“…Sin afán de exhaustividad señalaremos que hay datos que indican la presencia de traumatismos en los trastornos disociativos (Gershimy y Thayer, 1999;Pérez y Galdón, 2003), los trastornos de personalidad, espedalmoite el limite (Sabo, 1997), la bulimia y otros trastornos alimentarios (Everyll y Waller, 1995;Everyll, Waller y MacDonald, 1995;Terr, 1995), los trastornos de ansiedad (Mancini, Van Ameringen y MacMillan, 1995), los trastornos del estado de animo (Hall, Sachs, Ráyeos y Lutenbacher, 1993), el alcoholismo (Windle, Windle, Scheidt y Miller, 1995) y muchos otros (véase para una revisión completa el texto de Everly y Latíng (1995).…”
Section: Planteamientos Previosunclassified